ANALISIS JARINGAN PENIPUAN ONLINE MELALUI MEDIA SOSIAL BERKEDOK PROSTITUSI (Studi Kasus kelompok X, Y dan Z di Kota Pekanbaru) - Desrajayu, Aditya; Fakhri Usmita (UIR PRESS, 2025)
This study examines the phenomenon of online fraud disguised as prostitution via social media, with a case study on groups X, Y, and Z in the city of Pekanbaru. The fraud was conducted using digital platforms such as Twitter, exploiting the ease of access and weak oversight of sexually explicit content. This research employs a descriptive qualitative approach, gathering data through interviews with perpetrators and analyzing their modus operandi. The findings reveal that each group played a distinct but interconnected role within the fraud network: Group X was responsible for targeting victims, Group Y approached and manipulated them, and Group Z acted as the receiver of the fraudulent proceeds. The analysis draws upon Sutherland’s Differential Association Theory, which posits that deviant behavior is learned through social interaction. Furthermore, the phenomenon is influenced by media convergence, which enables the integration of technologies and broadens the perpetrators’ reach across national boundaries. The study underscores the urgency of digital supervision and the need for preventive strategies from law enforcement and social media platforms to combat similar crimes.